Outcomes of parathyroidectomy in renal hyperparathyroidism in patients with No access to renal transplantation in Singapore. (January 2016) - Rajeev, Parameswaran; Lee, Kai Yin; Tang, Xin Jie; Goo, Tiong Thye; Tan, Wee Boon; Ngiam, Kee Yuan
Abstract: Background: Total parathyroidectomy with autotransplantation (TPTX + AT) and subtotal parathyroidectomy (SPTX) are considered standard surgical treatments for refractory renal hyperparathyroidism. However, there is little data available comparing their outcomes in an area with poor access to renal transplant and calcimimetics. Methods: Patients with renal hyperparathyroidism who underwent TPTX + AT and SPTX in a tertiary institution from 2006 to 2013 were studied. Patient characteristics, pre- and post-operative biochemical marker levels, and outcomes including recurrence rates, post-operative morbidity and mortality were analysed. Results: 87 patients underwent parathyroidectomy for renal hyperthyroidism. Transplant patients were excluded in this study. 81 patients were on long-term dialysis, with a median time of 7 years from initiation of haemodialysis to parathyroidectomy. 57 patients (70.4%) underwent TPTX + AT while 24 (29.6%) underwent SPTX. Post-operatively, there was significant decrease in parathyroid hormone (PTH), calcium and phosphate levels in both groups. PTH and phosphate levels were significantly lowered with TPTX compared to SPTX (p = 0.004, 0.003). Symptomatic hypocalcaemia was seen in both groups. In a median follow-up of 4 years, 11 patients developed biochemical recurrence, with a median time of 29 months to recurrence. Median PTH at recurrence was 67.1 pmol/L. Rate of recurrence was higher in patients who underwent SPTX (20.8% vs 10.5%), with a shorter median time to recurrence (median 62.1 vs 81.3 months). 2 patients required resection of the autograft. Cohort mortality was 11 patients (13.4%), with 3 deaths secondary to cardiovascular events. Conclusion: Total parathyroidectomy with autoimplantation is superior to subtotal parathyroidectomy in the short to intermediate term. Highlights: Retrospective cohort study of 81 dialysis patients undergoing subtotal (SPTX) and total parathyroidectomy (TPTX). Parathyroid hormone (PTH) and phosphate levels were significantly lowered in TPTX compared to SPTX ( p = 0.004, 0.003). Calcium levels significantly decreased in both groups but both groups had patients with symptomatic hypocalcaemia. 11 patients developed biochemical recurrence at a median follow up of 4 years with median PTH of 67.1 pmol/L at recurrence. Rate of recurrence was higher in patients who underwent SPTX (20.8% vs 10.5%).